A Randomized Controlled Trial of a Multimedia Patient Education Tool for Stress Versus Urgency Urinary Incontinence. Issue 7 (July 2021) - Schroeder, Michelle; Plotner, Elisabeth A.; Sharma, Shefali; Hunter, Krystal; Spector, Sean; Lipetskaia, Lioudmila
Abstract : Objective: The aim of this study was to determine whether there was a difference in patient education when comparing traditional conversation-based patient counseling with multimedia-based patient counseling about stress and urgency urinary incontinence. Methods: Patients seeking treatment for urinary incontinence were randomized to traditional, conversation-based counseling from a physician regarding stress and urgency urinary incontinence (control group) or view a video (multimedia) as their counseling (treatment group). A vignette-based assessment of the patient's knowledge of stress and urgency urinary incontinence was administered as a pretest, immediate posttest, and 6- to 8-week delayed posttest. The Incontinence Impact Questionnaire, short form, was used to assess quality of life and was administered at the initial visit and at the 6- to 8-week follow-up call. Patient satisfaction was recorded at the end of the initial visit using a continuous visual analog scale, and health literacy was evaluated using the Rapid Estimate of Adult Literacy in Medicine–Short Form or Short Assessment of Health Literacy–Spanish. Results: In the 98 participants, immediate posttest scores trended toward significance between the control and treatment groups ( P = 0.086). This trend was lost at the delayed posttest ( P = 0.122). Both methods of education showed a significant difference between pretest, immediate posttest, and delayed posttest ( P < 0.001). There were no demographic differences between groups. Conclusions: Multimedia-based patient education represents an effective method of providing patient education regarding urinary incontinence because those who received video education showed comparable comprehension of this topic when compared with standard physician counseling. Video education can feasibly be used as an alternative to, or in conjunction with, current patient education practices in a urogynecology setting. Abstract : Supplemental digital content is available in the text.